Multi-layer composite artificial cochlea electrode coating material with multiple anti-inflammatory and electrode-neuron repairing functions and preparation method of multi-layer composite artificial cochlea electrode coating material

Through multi-layer composite cochlear implant electrode coating material, inflammation and neuronal gap problems after cochlear implantation are solved, anti-inflammatory and neuronal repair are achieved, and auditory recovery is promoted.

CN120550199APending Publication Date: 2025-08-29ZHEJIANG UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510752140.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-06-06
Publication Date
2025-08-29

AI Technical Summary

Technical Problem

The inflammation caused by cochlear implantation and electrode and neuron gap problems caused by electrodes and neurons lead to the loss of residual listening hair cells and spiral ganglion cells in the cochlear, which in turn damages residual hearing and promotes fibrosis, forming a vicious cycle.

Method used

Multi-layer composite cochlear implant electrode coating materials, including silver elemental coating, ethylene glycol chitosan combined with bilirubin loaded on SilMA microgel and gold-copper clusterase loaded on porous GelMA hydrogel, combined with physical vapor deposition, vacuum ultra-short pulse laser processing, microfluidic control and mold casting technology, multiple anti-inflammatory and electrode-neuron repair functions were constructed.

Benefits of technology

It realizes the anti-inflammatory effect of the whole period after electrode implantation, maintains the homeostasis of the cochlea environment, reduces mechanical damage and fibrosis, promotes neuronal regeneration and differentiation, and improves auditory recovery effect.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120550199A_ABST
    Figure CN120550199A_ABST
Patent Text Reader

Abstract

The invention discloses a multi-layer composite artificial cochlea electrode coating material with multiple anti-inflammatory and electrode-neuron repairing functions and a preparation method of the multi-layer composite artificial cochlea electrode coating material. The preparation method specifically comprises the following steps: constructing a silver elementary substance coating on an artificial cochlea electrode platinum-iridium alloy contact base material by using a physical vapor deposition process; an electrode contact is obtained by combining a vacuum ultrashort pulse laser processing technology, and a methacrylated silk fibroin SilMA microsphere material loaded with bilirubin is prepared by a microfluidic technology; preparing gold-copper clustering enzyme by using a wet chemical reduction method; the preparation method comprises the following steps: preparing a porous methacrylated gelatin solution, composite neural stem cells, SilMA drug-loaded microspheres and gold-copper clustered enzyme; after in-situ curing and demolding are carried out on the surface of the artificial cochlea electrode by combining a mold pouring method, a multi-layer composite artificial cochlea electrode coating material with multiple anti-inflammatory and electrode-neuron repairing functions is obtained on the surface of the electrode, and the coating can provide a cell source for nerve deafness repairing and complete electrode-neuron repairing; and multiple anti-inflammatory functions are realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a preparation technology of a functional composite coating material, and in particular to a multi-layer composite cochlear implant electrode coating material with multiple anti-inflammatory and electrode-neuron repair functions and a preparation method thereof. Background Art

[0002] Cochlear implantation is currently the main way to restore hearing to patients with severe / profound sensorineural hearing loss. However, the inevitable mechanical damage to the cochlear implant electrodes during implantation, as well as the continuous stimulation generated by the implant itself as a foreign body in the inner ear, often induce acute and chronic inflammatory responses in the cochlea. At the same time, tissue damage and inflammation are accompanied by the generation of large amounts of reactive oxygen species (ROS). These two factors persist in the early stages of implantation and for a considerable period of time after implantation, leading to further loss of residual hair cells, spiral ganglion cells, and other normal cochlear cells in the cochlea, thereby impairing residual hearing. Continuous inflammatory responses also promote the fibrosis process in the cochlea, resulting in fibrous tissue wrapping around the electrodes. This wrapping not only increases the resistance of the electrodes, but also increases the required electrical stimulation intensity. Excessive electrical stimulation further damages the cochlear tissue, forming a vicious cycle.

[0003] Elemental silver has significant tissue anti-inflammatory ability. The present invention uses elemental silver as the coating material for the metal electrode contacts of the cochlear implant, which does not interfere with the conductivity of the electrode contacts. Its local immunomodulatory effect can maintain the homeostasis of the cochlear environment for a considerable period of time after electrode implantation.

[0004] BR is a metabolite of heme and an endogenous antioxidant. It exhibits cytoprotective and anti-inflammatory effects through its antioxidant properties. However, its insolubility in water limits its clinical application, and high concentrations of unbound BR are neurotoxic, further restricting its safety in clinical application. The present invention binds bilirubin to ethylene glycol chitosan, making BR water-soluble and effectively eliminating the neurotoxicity of free BR. On this basis, it is loaded into SilMA microgel and encapsulated in porous GelMA. As an electrode coating, it can achieve local precision drug delivery. The constructed dual sustained-release system can effectively prolong the local antioxidant effect of BR.

[0005] Gold-copper cluster enzyme is a bimetallic nanozyme with ultra-high catalytic activity. It exhibits multi-enzyme activity similar to superoxide dismutase, catalase, and peroxidase. It can effectively remove excess ROS in the body, maintain intracellular redox balance, and reduce the damage of oxidative stress to cell structure and function. Gold and copper, as the core metal atoms that constitute the cluster, have excellent chemical stability and inertness, and have a good biosafety basis. The present invention introduces gold-copper cluster enzyme into the coating of cochlear implant electrodes, effectively removing excess ROS in the cochlea after electrode implantation, inhibiting the oxidative stress cascade reaction from the source, and reducing cochlear tissue damage.

[0006] Cochlear implant electrodes produce hearing by directly stimulating the residual spiral ganglion cells in the cochlea, so the number and function of nerve cells will determine the hearing improvement effect after cochlear implantation. However, as non-regenerative cells, lost neurons cannot be replenished. The present invention achieves neuronal regeneration and repair at the same time as cochlear implantation by three-dimensionally loading neural stem cells in the porous GelMA electrode coating, thereby promoting hearing recovery. Porous GelMA has good biocompatibility, and its loose pore structure is also conducive to the growth and differentiation of neural stem cells loaded therein and the extension of axons. Summary of the Invention

[0007] The purpose of the present invention is to provide a multi-layer composite cochlear implant electrode coating material with multiple anti-inflammatory and electrode-neuron repair functions and a preparation method thereof to address the problems of inflammation caused by cochlear implant insertion and the difficulty of patients in achieving "good hearing" due to the gap between the cochlear implant electrode and neurons. The material provides a cell source for the repair of sensorineural hearing loss and completes electrode-neuron repair, and has multiple anti-inflammatory functions, which can realize the innovation of cochlear implants.

[0008] The present invention is achieved by adopting the following technical solutions:

[0009] A method for preparing a multilayer composite cochlear implant electrode coating material with multiple anti-inflammatory and electrode-neuron repair functions, the preparation process is as follows:

[0010] 1) Using physical vapor deposition (PVD) technology to construct a silver coating on a cochlear implant electrode metal alloy contact substrate, then combining vacuum ultrashort pulse laser processing technology to obtain electrode contacts, and assembling the electrode contacts into the cochlear implant electrode to obtain a cochlear implant silver coating electrode;

[0011] 2) preparing ethylene glycol chitosan conjugated to bilirubin, and preparing methacrylylated silk fibroin SilMA drug-loaded microspheres loaded with ethylene glycol chitosan conjugated to bilirubin by microfluidic technology;

[0012] 3) Gold-copper cluster enzyme was prepared by wet chemical reduction method;

[0013] 4) preparing a porous methacrylated gelatin solution, compounding neural stem cells, the SilMA drug-loaded microspheres, and the gold-copper clustering enzyme in the gelatin solution to obtain a cochlear implant electrode coating pre-solution;

[0014] 5) The cochlear implant electrode coating pre-solution is combined with the mold casting method to in situ solidify the surface of the cochlear implant silver element coating electrode obtained in step 1) to form a cell-laden composite gel electrode coating, and finally a multilayer composite cochlear implant electrode coating material with multiple anti-inflammatory and electrode-neuron repair functions is obtained on the surface of the cochlear implant electrode.

[0015] Furthermore, the physical vapor deposition (PVD) process in step 1) is used to construct a silver coating on the cochlear implant electrode as follows:

[0016] Use PVD equipment with a power of 180-250W and equipped with silver target. Heat the cavity to 150-180℃, place the cochlear implant electrode in the sputtering chamber, evacuate to 1-8Pa, turn on the ion source, and rotate the cochlear implant electrode clockwise at a rate of 5-15r / min. 2 The surface of the cochlear implant electrode was bombarded and cleaned. After cleaning, the ion source was turned off, 35-45 sccm of argon was injected, the cavity pressure was maintained at 0.5-2.0 Pa, and a negative bias of -50 V was applied for sputtering to obtain a 10-20 μm silver elemental coating.

[0017] Furthermore, in step 1), the electrode contacts are obtained by combining vacuum ultrashort pulse laser processing technology as follows:

[0018] Using an ultraviolet femtosecond laser processing system, the cochlear implant electrode with a silver single substance coating deposited on the surface was placed in a vacuum reactor and the vacuum degree was 10 -4 -10 -5 In the Pa environment, 5-10 sccm of high-purity argon was injected for protection, and the energy density of the ultraviolet femtosecond fiber laser was adjusted to 0.3-0.7 J / cm 2 , repetition frequency 100-420kHz, set UV wavelength 355nm, pulse width 300-500fs, spot diameter 15-30μm, scan at an average speed of 500-1500mm / s, perform at least 3 layered scans and then cut to obtain electrode contacts, and finally at 0.1J / cm 2 A single scan is performed on the edge of the electrode contact under energy density conditions to achieve low-power polishing of the electrode contact.

[0019] Furthermore, step 2) is specifically as follows:

[0020] Under room temperature and in the dark, bilirubin (BR) is completely dissolved in dimethyl sulfoxide (DMSO), and 1-ethyl-3-(3-dimethylaminopropyl) carbodiimide (EDC) and N-hydroxysuccinimide (NHS) are added in sequence, stirred for reaction, and then added dropwise to ethylene glycol chitosan (GC) solution, and the reaction is continued with stirring. After dialysis and freeze-drying, ethylene glycol chitosan-bound bilirubin (GC-BR) is obtained; methacryloylated silk fibroin (SilMA) is stirred and dissolved in a PBS solution containing a photoinitiator to obtain a SilMA solution, and the GC-BR is added to the SilMA solution and stirred to disperse uniformly to prepare a dispersed phase; mineral oil containing Span80 is used as a continuous phase, and pre-gel microspheres are prepared by microfluidic technology, and cured microspheres are obtained by ultraviolet curing device, and washed to obtain GC-BR / SilMA microspheres, i.e., methacryloylated silk fibroin SilMA drug-loaded microspheres loaded with ethylene glycol chitosan-bound bilirubin;

[0021] The concentration of BR in DMSO is 1-3wt%, and the final concentration after mixing in GC solution is 0.1-0.3wt%; the concentration of EDC is 1-2wt%, the concentration of NHS is 0.5-1.5wt%; the concentration of GC is 1-3wt%; the molecular weight cutoff of the dialysis bag used for dialysis is 3500-7000Da; the concentration of SilMA is 10-20wt%; the photoinitiator is one of Irgacure and lithium phenyl-2,4,6-trimethylbenzoylphosphinate (LAP), with a concentration of 0.5-1.0wt%; the concentration of GC-BR in SilMA solution is 1-2wt%; the microfluidic device, the continuous phase Span in mineral oil 80 concentration is 2-5wt%, the dispersed phase flow rate is controlled to be 15-30μL / min, and the continuous phase flow rate is controlled to be 80-150μL / min; the UV curing device has an irradiation time of 15-30s, a light source wavelength of 350-410nm, and a power of 20-40mW / cm 2 The washing step specifically involves washing the microspheres in sequence with acetone, 75% ethanol and PBS solution.

[0022] Furthermore, in step 3), the gold-copper cluster enzyme is prepared by wet chemical reduction, specifically:

[0023] A gold chlorate solution and a copper nitrate solution are prepared and mixed, mercaptopropionic acid (MPA) is added to the mixed solution, and the mixture is stirred at room temperature to obtain a thiol-metal ion pre-binding solution reaction system; a sodium hydroxide solution is then added to the reaction system; a sodium borohydride sodium hydroxide solution is prepared and added to the reaction system, and the reaction is stirred at room temperature in the dark; the reaction system is transferred to a 4°C refrigerator and aged in the dark for 12-18 hours; free small molecules and large particles are removed by ultrafiltration; and the gold-copper cluster enzyme is obtained by freeze-drying.

[0024] The gold chlorate concentration in the thiol-metal ion pre-binding solution is 2-3 mM, the copper nitrate concentration is 0.05-0.1 mM, and the MPA concentration is 4-5 mM; the concentration of the sodium hydroxide added to the reaction system is 100-110 mM; the sodium borohydride sodium hydroxide solution is prepared by adding sodium borohydride to the sodium hydroxide solution, with the sodium borohydride concentration being 100-120 mM and the sodium hydroxide concentration being 0.1-0.4 M; the final concentration of the sodium borohydride added to the reaction system is 4-6 mM; the molecular weight cutoffs of the ultrafiltration centrifuge tube used in the ultrafiltration are 2-5 kDa and 8-12 kDa, respectively, to remove free small molecules and large particles; the centrifugal speed is 3000-5000 rpm, and the ultrafiltration is performed at least twice.

[0025] Furthermore, step 4) is specifically as follows:

[0026] Under light-proof conditions, the porous GelMA was added to a PBS solution and dissolved under magnetic stirring in a 37°C water bath to obtain a porous GelMA solution; the SilMA drug-loaded microspheres and the gold-copper cluster enzyme were dispersed in the porous GelMA solution to obtain a composite porous GelMA solution; neural stem cells were collected, added to the composite porous GelMA solution, and the cells were resuspended by blowing to disperse them in the composite solution to obtain a cochlear implant electrode coating pre-solution.

[0027] Furthermore, the porous GelMA has a substitution degree of 30-60%, and the prepared solution concentration is 5-10 wt%;

[0028] The SilMA drug-loaded microspheres have a concentration of 0.5-1.0 wt%; the gold-copper cluster enzyme has a concentration of 0.005-0.05 wt%;

[0029] The neural stem cells are differentiated from induced pluripotent stem cells. After continuous passage to 3-5 generations, the neural stem cells are loaded on porous GelMA and resuspended in the composite porous GelMA solution in an amount of 0.1-10×10 7 mL -1 .

[0030] Furthermore, step 5) is specifically as follows:

[0031] Under light-proof conditions, the silver-coated cochlear implant electrode prepared in step 1) is placed in a casting mold, and the electrode is fixed in the mold using the positioning beads on the electrode itself; the electrode gel coating pre-solution prepared in step 4) is poured into the mold while oscillating to remove bubbles, and the mold and the electrode therein are exposed to a UV light source to complete the curing of the gel coating. After demolding, a multilayer composite cochlear implant electrode coating material with multiple anti-inflammatory and electrode-neuron repair functions is obtained on the electrode surface;

[0032] The casting mold is made of transparent quartz glass or PMMA, and is conical in shape, hollow, with a closed tip and an open bottom, capable of housing electrodes and casting coatings. The tip diameter is approximately 0.3-0.5 mm, and the bottom diameter is approximately 1.0-1.5 mm. The UV light source has a wavelength of 350-410 nm and a power of 20-40 mW / cm 2 , the exposure time is 30-60s, and the mold is placed 3-5cm away from the UV light source.

[0033] A multilayer composite cochlear implant electrode coating material with multiple anti-inflammatory and electrode-neuron repair functions is obtained by adopting the preparation method.

[0034] A cochlear implant electrode, the surface of which is coated with the multi-layer composite cochlear implant electrode coating material having multiple anti-inflammatory and electrode-neuron repair functions.

[0035] Compared with the prior art, the present invention has the following advantages:

[0036] 1) The present invention uses ethylene glycol chitosan, BR, SilMA, gold chlorate, copper nitrate, neural stem cells, etc. as raw materials, and combines physical vapor deposition, high-precision vacuum ultrashort pulse laser processing, microfluidics, wet chemical reduction, mold casting and other combined processes to produce a multi-layer composite cochlear implant electrode coating material with multiple anti-inflammatory and electrode-neuron repair functions. The above raw material selection and process combination are original to the present invention.

[0037] 2) The present invention uses elemental silver to construct a highly conductive electrode contact coating, and constructs a functional composite coating based on porous GelMA hydrogel in situ on the electrode surface. The composite material is loaded with glycol chitosan combined with BR, gold-copper cluster enzyme and neural stem cells, and has short-term high-efficiency anti-inflammatory and antioxidant, long-term immune microenvironment regulation, and cochlear nerve regeneration and repair functions. Among them, gold-copper cluster enzyme has ultra-high catalytic activity that is superior to natural antioxidants. It is loaded on the surface of the cochlear implant electrode with porous GelMA hydrogel as a matrix, which can achieve local antioxidant function synchronized with electrode implantation. Based on its atomic size and good dispersibility, it can be quickly released in the porous GelMA hydrogel coating after electrode implantation, exerting a significant anti-oxidative damage effect in the cochlea in the early stage of implantation (first anti-inflammatory effect). BR is an endogenous anti-inflammatory antioxidant substance. Ethylene glycol chitosan combined with BR is loaded in SilMA microgel and further encapsulated in porous GelMA hydrogel to construct a BR dual sustained-release platform, which can maintain local anti-inflammatory and antioxidant effects for a long time after electrode implantation (second anti-inflammatory effect). A dense, continuous and stable single silver coating is deposited on the surface of the electrode contact, which not only improves the conductivity of the electrode, but also exerts its anti-inflammatory effect locally, and maintains the homeostasis of the cochlear immune environment for a long time (the third anti-inflammatory). The double-coated cochlear implant electrode prepared by the present invention can achieve full-time anti-inflammatory effect after implantation, maintain the stability of the internal environment, and reduce the damage to the residual functional cells of the cochlea caused by inflammation and oxidative damage caused by mechanical damage to the implant, long-term foreign body reaction, etc. The present invention loads neural stem cells into the porous GelMA hydrogel electrode coating. The coating is both a loading tool for fixed-point transplantation of stem cells in vivo, avoiding the disordered diffusion and migration of stem cells in the cochlea; and as an extracellular matrix, it effectively promotes the differentiation of neural stem cells and axon extension to supplement neurons, overcoming the problem that the effect of cochlear implantation depends on the residual spiral ganglion cells. At the same time, the anti-inflammatory system constructed by the composite electrode effectively protects the transplanted neural stem cells, which is beneficial to their survival and differentiation.

[0038] 3) The present invention uses porous GelMA as the surface coating matrix of the cochlear implant electrode. On the one hand, the soft gel layer can reduce the friction and damage between the coating and the internal auditory canal, avoiding inflammation and fibrosis that are easily caused by cochlear implantation. Secondly, the porous GelMA can provide a spatial channel for the migration and axon extension of the stem cells loaded in the matrix through its rich internal pore structure; at the same time, after the electrode is implanted, it exists in the form of embracing the modiolus. The neural stem cells in the electrode coating will approach the modiolus and the basement membrane extending thereon along with the electrode, providing the required factors for neuronal differentiation, and more effectively promoting neuronal differentiation; the cells in the neural stem cell gel electrode layer are induced by the factors on the basement membrane and migrate in a directional manner through the pore structure inside the porous GelMA, which can eliminate the gap between the electrode and the neurons and provide a new approach for the treatment of sensorineural hearing loss. Moreover, the internal pore structure also provides a "shortcut" for the penetration of gold-copper cluster enzymes and bilirubin-loaded microspheres, so that the purpose of efficient anti-inflammatory can be achieved in the early stage.

[0039] 4) The present invention utilizes a physical vapor deposition process to produce a dense and uniform silver coating. The high-precision vacuum ultrashort pulse laser processing technology used has extremely high cutting accuracy and dimensional consistency, with minimal thermal damage, and cutting under vacuum conditions will not cause oxidation and ablation of the silver element, thereby ensuring the chemical stability, integrity and functionality of the silver coating and achieving a long-term anti-inflammatory effect of the electrode. Bilirubin is grafted onto ethylene glycol chitosan molecules using chemical grafting technology, and bilirubin-loaded SilMA microspheres are prepared by microfluidic technology to achieve gentle and uniform encapsulation of bilirubin, maximizing the retention of drug activity. The physical steric structure brought about by chemical grafting and microspheres achieves stable and long-lasting sustained release of the drug, making the anti-inflammatory process more durable and stable. Gold-copper cluster enzymes are prepared using a wet chemical reduction process. The obtained gold-copper cluster enzymes have the advantages of small size, strong activity, and good dispersibility. Encapsulation in the electrode hydrogel coating can achieve rapid release after implantation and efficient antioxidant effects. Combined with a mold casting process, the drug-loaded microgel, gold-copper cluster enzyme, neural stem cells, and porous GelMA hydrogel are integrated on the electrode surface, ensuring the coordinated expression of biological functions and perfectly conforming the coating to the electrode surface shape, resulting in a continuous and complete electrode coating. This supports quality consistency and improved production efficiency during industrial application. These processes support each other and synergize to create a multi-layer composite coating electrode for cochlear implants that possesses multiple biological functions, a precise and controllable structure, and supports industrial production needs.

[0040] 5) BR's extremely low water solubility and potential neurotoxicity limit its clinical application. The present invention grafts it onto ethylene glycol chitosan to obtain bound BR, which not only gives BR good water solubility but also effectively shields the risk of accumulation and toxic side effects of free BR in the nervous system. It has good biosafety and is suitable for the inner ear tissue with delicate structure and sensitive microenvironment.

[0041] 6) The cochlear implant electrode coating in the present invention is designed as a multi-layer composite structure, wherein the bottom layer of the electrode coating is a silver single substance coating, and the surface layer is a porous GelMA layer composited with neural stem cells, SilMA drug-loaded microspheres and gold-copper cluster enzymes. The silver single substance coating is directly compounded with the surface of the cochlear implant electrode as a base coating. On the one hand, it will not affect the conductivity of the electrode. On the other hand, it can be anti-inflammatory through the slow release of silver ions. The design of the gel layer on the outer surface can firstly reduce the problem of friction damage between the electrode and human tissue during implantation. Secondly, the cells inside the porous gel can quickly migrate out to solve the problem of internal cell loss, and the internal SilMA drug-loaded microspheres and gold-copper cluster enzymes can also play a role faster by virtue of the physical position of the surface layer. The above structure is designed by the present invention in combination with the actual use scenarios of cochlear implants and the clinical problems currently faced. The structure is obviously innovative.

[0042] 7) The cochlear implant electrode coating preparation system constructed by the present invention has structural compatibility and process flexibility, and can be widely adapted to electrodes of various specifications and models, showing excellent preparation convenience and technical versatility. BRIEF DESCRIPTION OF THE DRAWINGS

[0043] Figure 1 This is a schematic diagram of the preparation process of a multi-layer composite cochlear implant electrode coating material with multiple anti-inflammatory and electrode-neuron repair functions according to an embodiment of the present invention.

[0044] Figure 2 This is a schematic diagram of a hydrogel coating casting mold according to an embodiment of the present invention. DETAILED DESCRIPTION

[0045] The present invention is further described below with reference to specific examples.

[0046] Comparative Example 1:

[0047] Uncoated, conventional cochlear implants were used as a control and implanted into the guinea pig cochlea. Cochlear tissue was examined one or eight weeks after implantation. One week after implantation, a large number of inflammatory cells, primarily neutrophils and macrophages, accumulated in the scala tympani. Basilar membrane staining revealed an approximately 18% loss of hair cells. Eight weeks after implantation, the inflammatory cell count decreased, with fibrotic tissue forming a ring around the electrode. Inflammatory cells, primarily macrophages, were observed encapsulating the electrode. The fibrotic tissue occupied approximately 63% of the cross-sectional area of ​​the scala tympani. Basilar membrane staining revealed an approximately 24% loss of hair cells.

[0048] Example 1:

[0049] 1) Using a PVD device with a power of 200W and equipped with a 99.99% high-purity silver target, the chamber was heated to 180°C, the cochlear implant electrode platinum-iridium alloy contact substrate was placed in the sputtering chamber, the vacuum was evacuated to 1 Pa, the ion source was turned on, the sample was rotated clockwise at a rate of 10 r / min, and the current density was 0.4 A / cm 2 The sample surface was bombarded and cleaned for 15 minutes. After cleaning, the ion source was turned off, 40 sccm of argon was injected, the chamber pressure was maintained at 1 Pa, and a negative bias of -50 V was applied for sputtering for 40 minutes to obtain a 10-20 μm silver elemental coating.

[0050] 2) Using an ultraviolet femtosecond laser processing system, the platinum-iridium alloy contact substrate of the cochlear implant electrode with a silver single-element coating deposited on the surface was placed in a vacuum reactor and the vacuum degree was 10 -4 In the Pa environment, 10 sccm of high-purity argon was injected for protection, and the energy density of the ultraviolet femtosecond fiber laser was adjusted to 0.5 J / cm 2 , repetition frequency 300kHz, set UV wavelength 355nm, pulse width 400fs, spot diameter 15μm, scan at an average speed of 1000mm / s, perform 3 layered scans and then precisely cut to obtain electrode contacts, and finally at 0.1J / cm 2 A single scan is performed on the edge of the electrode contact under energy density conditions to achieve low-power polishing of the electrode contact, and the electrode contact is assembled into a cochlear implant electrode.

[0051] 3) Under light-proof conditions, BR was completely dissolved in DMSO to a concentration of 2wt%, 2wt% EDC and 1wt% NHS were added in sequence, and the mixture was stirred and reacted at room temperature in the dark for 1 hour. Subsequently, the mixture was added dropwise to a 2wt% GC solution to a concentration of 0.2wt% BR in the GC solution, and the mixture was stirred and reacted for 24 hours at room temperature in the dark. The mixture was dialyzed for 3 days and freeze-dried to obtain GC-BR. Under light-proof conditions, SilMA was stirred and dissolved in a PBS solution containing a photoinitiator to a concentration of 15wt%, and the GC-BR was added to the SilMA solution to a concentration of 2wt% GC-BR in the SilMA solution. The mixture was stirred to disperse the SilMA solution uniformly to prepare a dispersed phase. Pre-gel microspheres were prepared by microfluidic technology using mineral oil containing 3wt% Span 80 as the continuous phase. The dispersed phase flow rate was controlled at 20μL / min and the continuous phase flow rate was controlled at 120μL / min. The cured microspheres were obtained by UV curing with a UV irradiation time of 25s, a light source wavelength of 405nm, and a power of 35mW / cm 2 The microspheres were washed with acetone, 75% ethanol and PBS solution in sequence, and each detergent was washed 3 times to obtain GC-BR / SilMA microspheres, which are methacryloylated silk fibroin SilMA drug-loaded microsphere materials loaded with ethylene glycol chitosan and bilirubin.

[0052] 4) Prepare gold chlorate solution and copper nitrate solution, mix them, and add MPA to the solution. Stir at room temperature for 10 minutes to obtain a thiol-metal ion pre-conjugated solution with a gold chlorate concentration of 2.04 mM, copper nitrate concentration of 0.085 mM, and MPA concentration of 4.26 mM. Then, add sodium hydroxide solution to the above system, with the sodium hydroxide concentration in the reaction system being 109 mM. Dissolve sodium borohydride in sodium hydroxide solution to a sodium borohydride concentration of 113 mM and a sodium hydroxide concentration of 0.2 M. Rapidly add the above reaction system and stir at room temperature in the dark for 3 hours. Transfer the reaction system to a 4°C refrigerator and age in the dark for 12 hours. Remove free small molecules and larger particles using ultrafiltration centrifuge tubes with molecular weight cutoffs of 3 kDa and 10 kDa. Ultrafiltration is performed three times at 3500 rpm, respectively. The solution is then freeze-dried to obtain the gold-copper cluster enzyme.

[0053] 5) Under dark conditions, porous GelMA with a substitution degree of 30% was added to a PBS solution at a concentration of 6 wt%, and dissolved under magnetic stirring in a 37°C water bath for 1 h to obtain a porous GelMA solution; the solution was cooled to about 35°C, and under dark conditions, the prepared SilMA microspheres loaded with GC-BR and gold-copper clustering enzyme were dispersed in the porous GelMA solution, with a SilMA microsphere concentration of 1.0 wt% and a gold-copper clustering enzyme concentration of 0.01 wt%; neural stem cells differentiated from induced pluripotent stem cells were collected, and under dark conditions, the composite porous GelMA solution was added to the neural stem cells, and the cells were resuspended by pipetting to disperse them in the composite solution, with a cell density of 1×10 7 / mL to obtain the cochlear implant electrode coating pre-solution.

[0054] 6) Under light-proof conditions, the silver-coated electrode for the cochlear implant was placed in a casting mold and fixed in place in the mold using the positioning beads on the electrode itself. The mold was made of transparent quartz glass and had a conical shape, was hollow, had a closed tip, and was open at the bottom, which could accommodate the electrode and the coating. The tip diameter was approximately 0.4 mm and the bottom diameter was approximately 1.34 mm. The prepared coating pre-solution was poured into the mold while oscillating to remove bubbles. The mold and the electrode therein were exposed to a UV light source with a wavelength of 405 nm and a power of 35 mW / cm 2 The exposure time is 35s, and the electrode mold is placed 5cm away from the UV light source; after the gel coating is cured and demolded, a multilayer composite cochlear implant electrode coating material with multiple anti-inflammatory and electrode-neuron repair functions is obtained on the surface of the cochlear implant electrode. After combining with the cochlear implant electrode, a drug-loaded and stem cell-loaded composite hydrogel coating electrode with anti-inflammatory and neural repair functions in the cochlea is obtained.

[0055] 7) The composite-coated electrodes were implanted into the cochlea of ​​guinea pigs for one week. Inflammatory cells were visible in the cochlea, with the number of cells reduced by 76% compared to the control group. The inflammatory cells were mainly neutrophils and macrophages. Staining of the basement membrane revealed a significant decrease in hair cell loss, approximately 5%, compared to the control group. TUJ1 staining of the transplanted nerve cells revealed a significant increase in neuronal differentiation and axonal extension. Eight weeks after the composite-coated electrodes were implanted into the cochlea of ​​guinea pigs, a small amount of annular fibrotic tissue surrounding the electrodes was visible in the scala tympani, an 84% decrease compared to the control group. A small number of macrophages were visible in the fibrotic tissue. Staining of the basement membrane revealed a significant decrease in hair cell loss, approximately 8%, compared to the control group. TUJ1 staining of the transplanted nerve cells revealed that differentiated neurons were still visible in the cochlea, and nerve fibers were seen extending toward and contacting the basement membrane.

[0056] Example 2

[0057] 1) Using a PVD device with a power of 200W and equipped with a 99.99% high-purity silver target, the chamber was heated to 180°C, the cochlear implant electrode platinum-iridium alloy contact substrate was placed in the sputtering chamber, the vacuum was evacuated to 1 Pa, the ion source was turned on, the sample was rotated clockwise at a rate of 10 r / min, and the current density was 0.4 A / cm 2 The sample surface was bombarded and cleaned for 15 minutes. After cleaning, the ion source was turned off, 40 sccm of argon was injected, the chamber pressure was maintained at 1 Pa, and a negative bias of -50 V was applied for sputtering for 40 minutes to obtain a 10-20 μm silver elemental coating.

[0058] 2) Using an ultraviolet femtosecond laser processing system, the platinum-iridium alloy contact substrate of the cochlear implant electrode with a silver single-element coating deposited on the surface was placed in a vacuum reactor and the vacuum degree was 10 -4 In the Pa environment, 10 sccm of high-purity argon was injected for protection, and the energy density of the ultraviolet femtosecond fiber laser was adjusted to 0.5 J / cm 2 , repetition frequency 300kHz, set UV wavelength 355nm, pulse width 400fs, spot diameter 15μm, scan at an average speed of 1000mm / s, perform 3 layered scans and then precisely cut to obtain electrode contacts, and finally at 0.1J / cm 2 A single scan is performed on the electrode contact edge under energy density conditions to achieve low-power polishing of the electrode contact, and the electrode contact is assembled into the cochlear implant electrode.

[0059] 3) Under light-proof conditions, BR was completely dissolved in DMSO to a concentration of 2 wt%, and 2 wt%

[0060] EDC and 1 wt% NHS were stirred and reacted at room temperature in the dark for 1 hour, and then 2 wt%

[0061] In the GC solution, the concentration of BR in the GC solution is 0.2wt%, and the reaction is continued with stirring at room temperature in the dark for 24 hours, dialyzed for 3 days, and freeze-dried to obtain GC-BR. At room temperature in the dark, SilMA is stirred and dissolved in a PBS solution containing a photoinitiator at a concentration of 15wt%, and then the above-mentioned GC-BR is added to the SilMA solution, and the concentration of GC-BR in the SilMA solution is 2wt%. Stirring makes it dispersed evenly to prepare a dispersed phase; using mineral oil containing 3wt% Span 80 as the continuous phase, pre-gel microspheres are prepared by microfluidic technology, controlling the dispersed phase flow rate to 20μL / min, and the continuous phase flow rate to 120μL / min, and obtaining cured microspheres by ultraviolet curing device, with ultraviolet irradiation time of 25s, light source wavelength of 405nm, and power of 35mW / cm 2The microspheres were washed with acetone, 75% ethanol and PBS solution in sequence, and each detergent was used for washing 3 times to obtain GC-BR / SilMA microspheres.

[0062] 4) Under dark conditions, porous GelMA with a substitution degree of 30% was added to a PBS solution at a concentration of 6 wt%, and dissolved under magnetic stirring in a 37°C water bath for 1 h to obtain a porous GelMA solution; the solution was cooled to about 35°C, and under dark conditions, the prepared SilMA microspheres loaded with GC-BR were dispersed in the porous GelMA solution at a concentration of 1.0 wt%; neural stem cells differentiated from induced pluripotent stem cells were collected, and under dark conditions, the composite porous GelMA solution was added to the neural stem cells, and the cells were resuspended by pipetting to disperse them in the composite solution. The cell density in the solution was 1×10 7 / mL to obtain the cochlear implant electrode coating pre-solution.

[0063] 5) Under light-proof conditions, place the cochlear implant silver elemental coating electrode into a casting mold and secure the electrode in place in the mold using the positioning beads on the electrode itself. The mold is made of transparent quartz glass and has a conical shape, is hollow, has a closed tip, and an open bottom, allowing for placement of the electrode and casting the coating. The tip diameter is approximately 0.4 mm and the bottom diameter is approximately 1.34 mm. The prepared coating pre-solution is cast into the mold while oscillating to remove bubbles. The mold and the electrode therein are exposed to a UV light source with a wavelength of 405 nm and a power of 35 mW / cm 2 The exposure time is 35 seconds, and the electrode mold is placed 5 cm away from the UV light source; after the gel coating is cured and demolded, a composite coating material is obtained on the surface of the cochlear implant electrode, and a composite coating electrode is obtained after combining with the cochlear implant electrode.

[0064] 6) Compared with Example 1, gold-copper clusterase was not added to the composite coating of Example 2. The composite-coated electrode was implanted in the cochlea of ​​a guinea pig for one week. Inflammatory cells were observed in the cochlea. Compared with the control example, the number of cells decreased by 34%, but the number of inflammatory cells increased compared with Example 1. The inflammatory cells were mainly neutrophils and macrophages. Staining of the basement membrane showed a loss of approximately 11% of hair cells, which was a decrease compared with the control example, but an increase in hair cell loss compared with Example 1. Staining of the transplanted nerve cells using TUJ1 showed neuronal differentiation and axonal extension, but the number of neurons decreased by approximately 56% compared with Example 1. After implanting the composite-coated electrode into the guinea pig cochlea for 8 weeks, circular fibrotic tissue surrounding the electrode was observed in the scala tympani, which was 58% less than that of the control group, and a small number of macrophages were observed within the fibrotic tissue. Staining of the basement membrane revealed a loss of approximately 14% of hair cells, a decrease compared to the control group but an increase compared to Example 1. Using TUJ1 to stain the transplanted neural cells revealed a small number of differentiated neurons within the cochlea, a 64% decrease compared to Example 1, with a few nerve fibers extending toward and contacting the basement membrane. These results indicate that the loading of gold-copper cluster enzymes into the electrode coating can effectively reduce inflammatory cell infiltration, hair cell loss, and fibrosis formation within the cochlea after implantation, and can effectively protect the survival and differentiation of transplanted neural stem cells.

[0065] Example 3

[0066] 1) Using a PVD device with a power of 200W and equipped with a 99.99% high-purity silver target, the chamber was heated to 180°C, the cochlear implant electrode platinum-iridium alloy contact substrate was placed in the sputtering chamber, the vacuum was evacuated to 1 Pa, the ion source was turned on, the sample was rotated clockwise at a rate of 10 r / min, and the current density was 0.4 A / cm 2 The sample surface was bombarded and cleaned for 15 minutes. After cleaning, the ion source was turned off, 40 sccm of argon was injected, the chamber pressure was maintained at 1 Pa, and a negative bias of -50 V was applied for sputtering for 40 minutes to obtain a 10-20 μm silver elemental coating.

[0067] 2) Using an ultraviolet femtosecond laser processing system, the platinum-iridium alloy contact substrate of the cochlear implant electrode with a silver single-element coating deposited on the surface was placed in a vacuum reactor and the vacuum degree was 10 -4 In the Pa environment, 10 sccm of high-purity argon was injected for protection, and the energy density of the ultraviolet femtosecond fiber laser was adjusted to 0.5 J / cm 2 , repetition frequency 300kHz, set UV wavelength 355nm, pulse width 400fs, spot diameter 15μm, scan at an average speed of 1000mm / s, perform 3 layered scans and then precisely cut to obtain electrode contacts, and finally at 0.1J / cm 2A single scan is performed on the electrode contact edge under energy density conditions to achieve low-power polishing of the electrode contact, and the electrode contact is assembled into the cochlear implant electrode.

[0068] 3) Prepare gold chlorate solution and copper nitrate solution, mix them, and add MPA to the solution. Stir at room temperature for 10 minutes to obtain a thiol-metal ion pre-conjugated solution with a gold chlorate concentration of 2.04 mM, copper nitrate concentration of 0.085 mM, and MPA concentration of 4.26 mM. Then, add sodium hydroxide solution to the above system, with the sodium hydroxide concentration in the reaction system being 109 mM. Dissolve sodium borohydride in sodium hydroxide solution to a sodium borohydride concentration of 113 mM and sodium hydroxide concentration of 0.2 M. Rapidly add the above reaction system and stir at room temperature in the dark for 3 hours. Transfer the reaction system to a 4°C refrigerator and age in the dark for 12 hours. Remove free small molecules and larger particles using ultrafiltration centrifuge tubes with molecular weight cutoffs of 3 kDa and 10 kDa. Ultrafiltration is performed three times at 3500 rpm, respectively. The solution is then freeze-dried to obtain the gold-copper cluster enzyme.

[0069] 4) Under dark conditions, a porous GelMA with a substitution degree of 30% was added to a PBS solution at a concentration of 6 wt%, and dissolved under magnetic stirring in a 37°C water bath for 1 h to obtain a porous GelMA solution; the solution was cooled to about 35°C, and the prepared gold-copper clustering enzyme was dispersed in the porous GelMA solution under dark conditions, with the gold-copper clustering enzyme concentration being 0.01 wt%; neural stem cells differentiated from induced pluripotent stem cells were collected, and the composite porous GelMA solution was added to the neural stem cells under dark conditions, and the cells were resuspended by pipetting to disperse them in the composite solution, with a cell density of 1×10 7 / mL to obtain the cochlear implant electrode coating pre-solution.

[0070] 5) Under light-proof conditions, place the cochlear implant silver elemental coating electrode into a casting mold and secure the electrode in place in the mold using the positioning beads on the electrode itself. The mold is made of transparent quartz glass and has a conical shape, is hollow, has a closed tip, and an open bottom, allowing for placement of the electrode and casting the coating. The tip diameter is approximately 0.4 mm and the bottom diameter is approximately 1.34 mm. The prepared coating pre-solution is cast into the mold while oscillating to remove bubbles. The mold and the electrode therein are exposed to a UV light source with a wavelength of 405 nm and a power of 35 mW / cm 2 The exposure time is 35 seconds, and the electrode mold is placed 5 cm away from the UV light source; after the gel coating is cured and demolded, a composite coating material is obtained on the surface of the cochlear implant electrode, and a composite coating electrode is obtained after combining with the cochlear implant electrode.

[0071] 6) Compared with Example 1, SilMA drug-loaded microspheres loaded with GC-BR were not added to the composite coating of Example 3. The composite coating electrode was implanted into the cochlea of ​​a guinea pig for one week. Inflammatory cells were visible in the cochlea. Compared with the control example, the number of cells decreased by 38%, but compared with Example 1, the number of inflammatory cells increased, and the inflammatory cells were mainly neutrophils and macrophages. The basement membrane was stained, and the loss of hair cells was reduced by about 10% compared with the control example, but the loss of hair cells increased compared with Example 1. The transplanted nerve cells were stained with TUJ1, and a small number of differentiated neurons were seen in the cochlea, which was 53% less than that in Example 1. A small number of nerve fibers were seen extending toward and contacting the basement membrane. After implanting the composite-coated electrode into the guinea pig cochlea for 8 weeks, circular fibrotic tissue surrounding the electrode was observed in the scala tympani, which was 51% less than that of the control group, and a small number of macrophages were observed within the fibrotic tissue. Staining of the basement membrane revealed a decrease in hair cell loss of approximately 13% compared to the control group, but an increase compared to Example 1. TUJ1 staining of the transplanted neural cells revealed a small number of differentiated neurons within the cochlea, which was 60% less than that of Example 1, with a few nerve fibers extending toward and contacting the basement membrane. These results indicate that the loading of GC-BR / SilMA microspheres into the electrode coating effectively reduces inflammatory cell infiltration, hair cell loss, and fibrosis formation within the cochlea after implantation, and effectively protects the survival and differentiation of transplanted neural stem cells.

[0072] Example 4

[0073] 1) Under light-proof conditions, BR was completely dissolved in DMSO to a concentration of 2 wt%, and 2 wt%

[0074] EDC and 1 wt% NHS were stirred and reacted at room temperature in the dark for 1 hour, and then 2 wt%

[0075] In the GC solution, the concentration of BR in the GC solution is 0.2wt%, and the reaction is continued with stirring at room temperature in the dark for 24 hours, dialyzed for 3 days, and freeze-dried to obtain GC-BR. At room temperature in the dark, SilMA is stirred and dissolved in a PBS solution containing a photoinitiator at a concentration of 15wt%, and then the above-mentioned GC-BR is added to the SilMA solution, and the concentration of GC-BR in the SilMA solution is 2wt%. Stirring makes it dispersed evenly to prepare a dispersed phase; using mineral oil containing 3wt% Span 80 as the continuous phase, pre-gel microspheres are prepared by microfluidic technology, controlling the dispersed phase flow rate to 20μL / min, and the continuous phase flow rate to 120μL / min, and obtaining cured microspheres by ultraviolet curing device, with ultraviolet irradiation time of 25s, light source wavelength of 405nm, and power of 35mW / cm 2 The microspheres were washed with acetone, 75% ethanol and PBS solution in sequence, and each detergent was used for washing 3 times to obtain GC-BR / SilMA microspheres.

[0076] 2) Prepare gold chlorate solution and copper nitrate solution, mix them, and add MPA to the solution. Stir at room temperature for 10 minutes to obtain a thiol-metal ion pre-conjugated solution with a gold chlorate concentration of 2.04 mM, copper nitrate concentration of 0.085 mM, and MPA concentration of 4.26 mM. Then, add sodium hydroxide solution to the reaction system, with the sodium hydroxide concentration in the reaction system at 109 mM. Dissolve sodium borohydride in sodium hydroxide solution to a sodium borohydride concentration of 113 mM and a sodium hydroxide concentration of 0.2 M. Rapidly add the solution to the reaction system and stir at room temperature in the dark for 3 hours. Transfer the reaction system to a 4°C refrigerator and age in the dark for 12 hours. Remove free small molecules and larger particles using ultrafiltration centrifuge tubes with molecular weight cutoffs of 3 kDa and 10 kDa. Ultrafiltration is performed three times at 3500 rpm for each reaction. The solution is then freeze-dried to obtain the gold-copper cluster enzyme.

[0077] 3) Under dark conditions, porous GelMA with a substitution degree of 30% was added to a PBS solution at a concentration of 6 wt%, and dissolved under magnetic stirring in a 37°C water bath for 1 h to obtain a porous GelMA solution; the solution was cooled to about 35°C, and under dark conditions, the prepared SilMA microspheres loaded with GC-BR and gold-copper clustering enzyme were dispersed in the porous GelMA solution, with a SilMA microsphere concentration of 1.0 wt% and a gold-copper clustering enzyme concentration of 0.01 wt%; neural stem cells differentiated from induced pluripotent stem cells were collected, and under dark conditions, the composite porous GelMA solution was added to the neural stem cells, and the cells were resuspended by pipetting to disperse them in the composite solution, with a cell density of 1×10 7 / mL to obtain the cochlear implant electrode coating pre-solution.

[0078] 4) Under light-proof conditions, an ordinary artificial cochlear electrode that has not been treated with a silver elemental coating is placed in a casting mold. The electrode is fixed in the mold using the positioning beads on the electrode itself. The mold is made of transparent quartz glass and has a conical shape, is hollow, has a closed tip, and an open bottom. It can be used to place the electrode and cast the coating. The tip diameter is approximately 0.4 mm and the bottom diameter is approximately 1.34 mm. The prepared coating pre-solution is poured into the mold while oscillating to remove bubbles. The mold and the electrode inside are exposed to a UV light source with a wavelength of 405 nm and a power of 35 mW / cm 2 The exposure time is 35 seconds, and the electrode mold is placed 5 cm away from the UV light source; after the gel coating is cured and demolded, a composite coating material is obtained on the surface of the cochlear implant electrode, and a composite coating electrode is obtained after combining with the cochlear implant electrode.

[0079] Compared with Example 1, Example 3 uses a cochlear implant electrode without a silver single substance coating. The composite coating electrode was implanted into the guinea pig cochlea for 1 week, and inflammatory cells were visible in the cochlea. Compared with the control group, the cell number was reduced by 73%, and the inflammatory cells were mainly neutrophils and macrophages. The basement membrane was stained, and it was found that the loss of hair cells was significantly reduced by about 6% compared with the control group. The composite coating electrode was implanted into the guinea pig cochlea for 8 weeks. The fibrotic tissue around the electrode in the tympanic scala was observed, which was 37% less than that of the control group. Macrophages were seen in the fibrotic tissue. The basement membrane was stained, and the loss of hair cells was about 15%, which was less than that of the control group, but more than that of Example 1. The transplanted nerve cells were stained with TUJ1, and the differentiated neurons in the cochlea were observed. The number was reduced by 35% compared with that of Example 1. Neuronal differentiation and axon extension were observed. The results showed that GC-BR / SilMA microspheres and gold-copper cluster enzymes exerted significant anti-inflammatory effects in the early stage of electrode implantation, effectively protecting hair cells from immune damage. The electrode silver coating continued to exert anti-inflammatory effects for a long time after implantation, effectively reducing the loss of hair cells and fibrosis formation in the cochlea, and continuously protecting the survival and differentiation of transplanted neural stem cells.

Claims

1. A method for preparing a multilayer composite cochlear implant electrode coating material with multiple anti-inflammatory and electrode-neuron repair functions, characterized by: The preparation process is as follows: 1) Using physical vapor deposition (PVD) technology to construct a silver coating on a cochlear implant electrode metal contact substrate, then combining vacuum ultrashort pulse laser processing technology to obtain electrode contacts, and assembling the electrode contacts into the cochlear implant electrode to obtain a cochlear implant silver coating electrode; 2) preparing ethylene glycol chitosan conjugated to bilirubin, and preparing methacrylylated silk fibroin SilMA drug-loaded microspheres loaded with ethylene glycol chitosan conjugated to bilirubin by microfluidic technology; 3) Gold-copper cluster enzyme was prepared by wet chemical reduction method; 4) preparing a porous methacrylated gelatin solution, compounding neural stem cells, the SilMA drug-loaded microspheres, and the gold-copper clustering enzyme in the gelatin solution to obtain a cochlear implant electrode coating pre-solution; 5) The cochlear implant electrode coating pre-solution is combined with the mold casting method to in situ solidify the surface of the cochlear implant silver element coating electrode obtained in step 1) to form a cell-laden composite gel electrode coating, and finally a multilayer composite cochlear implant electrode coating material with multiple anti-inflammatory and electrode-neuron repair functions is obtained on the surface of the cochlear implant electrode.

2. The method for preparing a multilayer composite cochlear implant electrode coating material having multiple anti-inflammatory and electrode-neuron repair functions according to claim 1, characterized in that: In step 1), the physical vapor deposition (PVD) process for constructing a silver coating on the cochlear implant electrode is specifically as follows: Use PVD equipment with a power of 180-250W and equipped with silver target. Heat the cavity to 150-180℃, place the cochlear implant electrode in the sputtering chamber, evacuate to 1-8Pa, turn on the ion source, and rotate the cochlear implant electrode clockwise at a rate of 5-15r / min. 2 The surface of the cochlear implant electrode was bombarded and cleaned. After cleaning, the ion source was turned off, 35-45 sccm of argon was injected, the cavity pressure was maintained at 0.5-2.0 Pa, and a negative bias was applied for sputtering to obtain a 10-20 μm silver elemental coating.

3. The method for preparing a multilayer composite cochlear implant electrode coating material having multiple anti-inflammatory and electrode-neuron repair functions according to claim 1, characterized in that: In step 1), the electrode contacts are obtained by combining vacuum ultrashort pulse laser processing technology as follows: Using an ultraviolet femtosecond laser processing system, the cochlear implant electrode with a silver single substance coating deposited on the surface was placed in a vacuum reactor and the vacuum degree was 10 -4 -10 -5 In the Pa environment, 5-10 sccm of high-purity argon was injected for protection, and the energy density of the ultraviolet femtosecond fiber laser was adjusted to 0.3-0.7 J / cm 2 , repetition frequency 100-420kHz, set UV wavelength 355nm, pulse width 300-500fs, spot diameter 15-30μm, scan at an average speed of 500-1500mm / s, perform at least 3 layered scans and then cut to obtain electrode contacts, and finally at 0.1J / cm 2 A single scan is performed on the edge of the electrode contact under energy density conditions to achieve low-power polishing of the electrode contact.

4. The method for preparing the multi-layer composite cochlear implant electrode coating material having multiple anti-inflammatory and electrode-neuron repair functions according to claim 1, characterized in that: Step 2) is specifically as follows: Under room temperature and in the dark, bilirubin (BR) is completely dissolved in dimethyl sulfoxide (DMSO), and 1-ethyl-3-(3-dimethylaminopropyl) carbodiimide (EDC) and N-hydroxysuccinimide (NHS) are added in sequence and stirred for reaction. The mixture is then dropwise added to a glycol chitosan (GC) solution and stirred for reaction. The mixture is dialyzed and freeze-dried to obtain glycol chitosan-bound bilirubin (GC-BR). Methacryloylated silk fibroin (SilMA) is stirred and dissolved in a PBS solution containing a photoinitiator to obtain a SilMA solution, and the GC-BR is added to the SilMA solution and stirred to prepare a dispersed phase. Pre-gel microspheres are prepared by microfluidic technology using mineral oil containing Span 80 as a continuous phase, and cured microspheres are obtained by ultraviolet curing. The cured microspheres are washed to obtain GC-BR / SilMA microspheres, i.e., methacryloylated silk fibroin (SilMA) drug-loaded microspheres loaded with glycol chitosan-bound bilirubin. The concentration of BR in DMSO is 1-3wt%, and the final concentration after mixing in GC solution is 0.1-0.3wt%; the concentration of EDC is 1-2wt%, the concentration of NHS is 0.5-1.5wt%; the concentration of GC is 1-3wt%; the molecular weight cutoff of the dialysis bag used for dialysis is 3500-7000Da; the concentration of SilMA is 10-20wt%; the photoinitiator is one of Irgacure and lithium phenyl-2,4,6-trimethylbenzoylphosphinate (LAP), with a concentration of 0.5-1.0wt%; the concentration of GC-BR in SilMA solution is 1-2wt%; the microfluidic device, the continuous phase Span in mineral oil 80 concentration is 2-5wt%, the dispersed phase flow rate is controlled to be 15-30μL / min, and the continuous phase flow rate is controlled to be 80-150μL / min; the UV curing device has an irradiation time of 15-30s, a light source wavelength of 350-410nm, and a power of 20-40mW / cm 2 The washing step specifically involves washing the microspheres in sequence with acetone, 75% ethanol and PBS solution.

5. The method for preparing a multilayer composite cochlear implant electrode coating material having multiple anti-inflammatory and electrode-neuron repair functions according to claim 1, characterized in that: In step 3), the gold-copper cluster enzyme is prepared by wet chemical reduction, specifically: A gold chlorate solution and a copper nitrate solution are prepared and mixed, mercaptopropionic acid (MPA) is added to the mixed solution, and the mixture is stirred at room temperature to obtain a thiol-metal ion pre-binding solution reaction system; a sodium hydroxide solution is then added to the reaction system; a sodium borohydride sodium hydroxide solution is prepared and added to the reaction system, and the reaction is stirred at room temperature in the dark; the reaction system is transferred to a 4°C refrigerator and aged in the dark for 12-18 hours; free small molecules and large particles are removed by ultrafiltration; and the gold-copper cluster enzyme is obtained by freeze-drying. The gold chlorate concentration in the thiol-metal ion pre-binding solution is 2-3 mM, the copper nitrate concentration is 0.05-0.1 mM, and the MPA concentration is 4-5 mM; the concentration of the sodium hydroxide added to the reaction system is 100-110 mM; the sodium borohydride sodium hydroxide solution is prepared by adding sodium borohydride to the sodium hydroxide solution, with the sodium borohydride concentration being 100-120 mM and the sodium hydroxide concentration being 0.1-0.4 M; the final concentration of the sodium borohydride added to the reaction system is 4-6 mM; the molecular weight cutoffs of the ultrafiltration centrifuge tube used in the ultrafiltration are 2-5 kDa and 8-12 kDa, respectively, to remove free small molecules and large particles; the centrifugal speed is 3000-5000 rpm, and the ultrafiltration is performed at least twice.

6. The method for preparing a multilayer composite cochlear implant electrode coating material having multiple anti-inflammatory and electrode-neuron repair functions according to claim 1, characterized in that: Step 4) is specifically as follows: Under light-proof conditions, the porous GelMA was added to a PBS solution and dissolved under magnetic stirring in a 37°C water bath to obtain a porous GelMA solution; the SilMA drug-loaded microspheres and the gold-copper cluster enzyme were dispersed in the porous GelMA solution to obtain a composite porous GelMA solution; Neural stem cells were collected, added to the composite porous GelMA solution, and the cells were resuspended by pipetting to disperse them in the composite solution to obtain a cochlear implant electrode coating pre-solution.

7. The method for preparing a multilayer composite cochlear implant electrode coating material having multiple anti-inflammatory and electrode-neuron repair functions according to claim 6, characterized in that: The porous GelMA has a substitution degree of 30-60% and a prepared solution concentration of 5-10 wt%; The SilMA drug-loaded microspheres have a concentration of 0.5-1.0 wt%; the gold-copper cluster enzyme has a concentration of 0.005-0.05 wt%; The neural stem cells are differentiated from induced pluripotent stem cells. After continuous passage to 3-5 generations, the neural stem cells are loaded on porous GelMA and resuspended in the composite porous GelMA solution in an amount of 0.1-10×10 7 mL -1 .

8. The method for preparing a multi-layer composite cochlear implant electrode coating material having multiple anti-inflammatory and electrode-neuron repair functions according to claim 1, characterized in that: Step 5) is specifically as follows: Under light-proof conditions, the silver-coated cochlear implant electrode prepared in step 1) is placed in a casting mold, and the electrode is fixed in the mold using the positioning beads on the electrode itself; the electrode gel coating pre-solution prepared in step 4) is poured into the mold while oscillating to remove bubbles, and the mold and the electrode therein are exposed to a UV light source to complete the curing of the gel coating. After demolding, a multilayer composite cochlear implant electrode coating material with multiple anti-inflammatory and electrode-neuron repair functions is obtained on the electrode surface; The casting mold is made of transparent quartz glass or PMMA, has a conical shape, is hollow, has a closed tip and an open bottom, can accommodate electrodes and cast coatings, has a tip diameter of about 0.3-0.5 mm, and a bottom diameter of about 1.0-1.5 mm; the UV light source has a wavelength of 350-410 nm and a power of 20-40 mW / cm 2 , the exposure time is 30-60s, and the mold is placed 3-5cm away from the UV light source.

9. A multi-layer composite cochlear implant electrode coating material with multiple anti-inflammatory and electrode-neuron repair functions, characterized in that: The method is as described in any one of claims 1 to 8.

10. A cochlear implant electrode, characterized in that: The electrode surface adopts the multi-layer composite cochlear implant electrode coating material with multiple anti-inflammatory and electrode-neuron repair functions as claimed in claim 9.